2016
DOI: 10.1159/000441786
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Maternal Characteristics during Early Pregnancy, Fetal Growth Rate and Newborn Weight in Healthy Pregnancies

Abstract: Background: The objective of this study was to evaluate the association between maternal characteristics in early pregnancy and fetal growth (FG) and birth weight (BW). Methods: A prospective cohort study was performed in unselected pregnant women who attended an ultrasound evaluation at 11-14 weeks of pregnancy. Medical history, biochemical blood tests, biophysical variables and fetal weight at 20-25 and 30-36 weeks as well as the BW were assessed. Bivariate and multivariate linear models were constructed. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Prepregnancy BMI had a positive association with the slope of EFW but not fetal head circumference, an index of early brain growth. While far from definitive, maternal prepregnancy or pregnancy BMI has been associated with greater fetal physical or head size in women with obesity compared with women with reference weight, 1 , 35 , 36 broadly consistent with our findings. In the neonatal period, prepregnancy BMI was associated with greater local thalamic connectivity and lower frontothalamic connectivity.…”
Section: Discussionsupporting
confidence: 89%
“…Prepregnancy BMI had a positive association with the slope of EFW but not fetal head circumference, an index of early brain growth. While far from definitive, maternal prepregnancy or pregnancy BMI has been associated with greater fetal physical or head size in women with obesity compared with women with reference weight, 1 , 35 , 36 broadly consistent with our findings. In the neonatal period, prepregnancy BMI was associated with greater local thalamic connectivity and lower frontothalamic connectivity.…”
Section: Discussionsupporting
confidence: 89%
“…The adjusted model additionally included maternal age, parity, education level, pre‐pregnancy BMI, smoking and alcohol consumption during pregnancy and total energy intake. 4 , 5 , 6 , 7 , 44 , 45 , 46 , 47 These possible confounders were selected based on associations with exposure and outcomes in the existing literature. As previous analyses in the same cohort did not show any differences in metabolite concentrations between boys and girls, 35 and including infant sex in the models did not change the effect estimates, we did not include this factor in our models.…”
Section: Methodsmentioning
confidence: 99%
“… 1 , 2 , 3 Adverse maternal lifestyle and metabolic factors such as poor diet quality, a high total energy intake, inadequate macro‐ and micronutrient intake, and underweight and obesity, adversely affect the intrauterine environment and foetal nutrient availability for foetal growth and development, leading to increased risks of pre‐term birth, SGA and LGA. 4 , 5 , 6 , 7 Adaptations in maternal and foetal metabolic pathways underlie at least part of the associations between adverse maternal factors and pre‐term birth, SGA and LGA. Thus far, studies mainly focused on conventional biomarkers of metabolic status, such as glucose, insulin and lipid concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Russia has also found a significant association between maternal early pregnancy BMI and risk of preterm birth (Sharashova, Anda, & Grjibovski, 2014). A previous Chilean study has demonstrated that there was a statistically significant association between maternal BMI in early pregnancy and birth weight of the newborn (Caradeux et al, 2016). It is well known that socio-economic factors including income, economy and educational level of mothers are associated with adverse pregnancy outcomes.…”
Section: Factors Affecting Pregnancy Outcomesmentioning
confidence: 97%